Standar Operasional Prosedur (SOP) Izin Investasi Dalam Meningkatkan Minat Investor Di Kota Depok - Siti Nurchalizah; Sri Ernawati (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
The research data processed is from the results of in-depth interviews or in-depth interviews for informants. The data sample was taken by snowball sampling. Data processing and analysis using SWOT. From the results of data processing, it was found that the internal and external matrices were compiled from the total score of the IFE (internal factor evaluation) and EFE (external factor evaluation) matrices which were valued (2.955 and 3.08). This can show that the position of the Standard Operating Procedure for investment permit procedures in increasing investor interest in the Depok City - West Java Investment and One-Stop Integrated Services Service is in square II, which is this position shows that the Standard Operating Procedure for investment permits in increasing investor interest in the Department. Investment and One-Stop Integrated Services for Depok City - West Java is growing and developing.